Air-conditioning of a typical house in moderate climates with Ground Source Heat Pumps and cost comparison with Air Source Heat Pumps - Christodoulides, Paul; Aresti, Lazaros; Florides, Georgios A. (My University, 2019)
The recent evolution of the Ground Source Heat Pumps (GSHPs) has initiated the debate whether it is economically feasible to install a GSHP as an alternative to an Air Source Heat Pump (ASHP). A typical house heating/cooling load for moderate climates is presented and discussed for comparison purposes. For this purpose, the thermal response of the Ground Heat Exchanger (GHE) and the estimated characteristics of the GSHP, based on existing experimental data and simulations in summer and winter through a CFD model are presented. The computed power rejected to the ground from the GSHP is discussed in relation to the HP characteristics at different operating temperatures, which affect the efficiency. More than one borehole for the GHE may be needed for the reduction of the temperature. Finally, a cost analysis is presented for different length GSHP systems and a comparison of the total energy savings is obtained. ASHP systems with the specifically designed, inverter technology ducted series HP are proven to be highly competitive with GSHP systems, which fail to be a clear viable investment for energy saving.
Keywords: GHE cost analysis; GHE in moderate climate; Ground heat exchangers; Ground Source Heat Pump Systems; GSHP in Cyprus